The Relationship Between Age Of Menarche And Parity With The Incidence Of Breast Cancer In The Oncology Surgery Room Of General Ahmad Yani Regional Hospital, Metro City - Qothrunnadaa, Qoonitah; Sadiman, Sadiman; Fairus, Martini (Universitas Dharmawangsa Medan, 2026)
Breast cancer is a disease in which breast cells grow uncontrollably and form tumors. Breast cancer is a non-communicable disease but is a deadly disease for women, (WHO, 2024) According to the World Health Organization (WHO) in 2022, there were 2.3 million women diagnosed with breast cancer. Based on Globocan data in 2020, the number of new cases of breast cancer in Indonesia in 2020 reached 16.6% or 65,858 cases out of a total of 396,914 new cases. This study generally aims to determine the relationship between age at menarche and parity with the incidence of breast cancer in the Oncology Surgery Room of General Ahmad Yani Regional Hospital, Metro City. This study is a quantitative study with a case-control study design. Data collection was carried out through interviews and reviewing medical records. The case population was all mothers diagnosed with breast cancer in the Oncology Surgery Room, the control population was all mothers who were not diagnosed with breast cancer in the Oncology Surgery Room, the research sample consisted of 80 respondents consisting of 40 case samples and 40 control samples, taken by accidental sampling technique. The analysis used univariate analysis with frequency distribution and bivariate analysis using the chi square test by determining the 95% confidence level. The results of the study on mothers with breast cancer (case group) obtained a proportion of menarche age of 65% and a proportion of parity of 55.0%. The results of the statistical test showed a relationship between menarche age p value = 0.007 and OR 3.857 and parity p value = 0.001 and OR = 5.762. The conclusion of the study is that there is a relationship between menarche age and parity with the incidence of breast cancer. Researchers hope that hospitals can provide education to patients and the community regarding menarche age, parity and other risk factors related to breast cancer in order to minimize the occurrence of breast cancer